O uso político das redes sociais online nas eleições de 2018 no Brasil - Lemos, Joelma Galvão de (2023)
This doctoral thesis it’s inserted in the discussions and studies about the Internet and online social networks, as well as on the social, political, economic and subjective changes caused by them and the political use of networks in the 2018 Brazilian elections. Elections showed how the architecture of networks can enable their use to promote fake news, polarization and even extremist political positions. And they made clear the need to deal with these issues, in order to find ways to enable an architecture that fosters and values the dialogue, the circulation of the word and democratic social relations as thought by cybernecticists and not the opposite. This study was developed from the psychoanalytic framework, through a reading-lintening of the bibliographic study regarding online social networks and their political use in the 2018 elections.